The relationship of an instrumented T-group and personality changes in self-concept and self-actualization : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Clarke-Woolley, Cheryl (Massey University, 1976)
The effectiveness of a self-administered, instrumented, sensitivity training method (PROCESS) was examined in terms of personality and changes in self-concept and self-actualization. Subjects included thirty-two third-year University students in Psychology, ten Nursing graduates in a University Nursing Studies programme, and five maximum security psychiatric patients. For the students, a marathon approach was used. A Case Study was made with the patients to subjectively compare group development in PROCESS to the developmental stages occurring in leader-led T- and Encounter groups. All three groups showed a decrease in discrepancy between their perceived Actual behaviour and their perceived Preferred behaviour from before to after their group experience. A holdout control procedure was used. The change was primarily accounted for by a change in Actual, and not Preferred behaviour. All three groups increased their mean scores on POI self-actualization scales, but the control groups' mean scores also increased over the experimental period. Women improved more than men in self-concept, but not in self-actualization. The predicted relationships between affiliation motivation and improvements in self-concept and self-actualization did not occur. Subjects with high PRF Affiliation did not improve more than subjects with low Affiliation. The PRF personality variables of Cognitive Structure and Social Recognition were negatively related to the pre- and post-measures, thus contaminating the findings. Rigid thinking and concern about others' attentions were related to lower self- concept and self-actualization scores. Difficulties with the Hawthorne effect, repeated testing with reflective measures, and the relationship of affiliation to Maslow's hierarchy, were discussed. Methodological, ethical, and theoretical problems with the study of self-administered, instrumented sensitivity groups were summarized. Adequate follow-up studies with behavioural criteria for effective changes as a result of experiencing groups seem to be the greatest need. In a subjective analysis of the group development, several stages of Bennis' and Shepard's, Schutz', and Tuckman's theories of group development were observed. PROCESS seems to be an innovative and viable alternative to traditional psychotherapeutic groups, with a more positive orientation, at least for normally intelligent patients as well as being an effective form of sensitivity training for university students.
Keywords: Self-actualization (Psychology); Self